Pengembangan Tim Kerja Yang Kolaboratif Dalam Manajemen Pendidikan Islam: Kajian Tematik Ayat Ayat Al-Qur’an - Vinna, Syevinna Alifia Dinta; Mirda, Merda Rahayu; Habib, Syafaatul Habib (Education Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to explore how Qur’anic principles can operationally foster a harmonious, productive, and sustainable team culture. This qualitative research employs a library research approach with thematic analysis, using the Qur’an as the primary source and relevant literature as secondary sources. The findings reveal six key principles: (1) ukhuwah Islamiyah, (2) shura (mutual consultation), (3) justice and non-discrimination, (4) amanah and responsibility, (5) tazkiyah al-nafs (self-purification), and (6) evaluation and  collective reflection. These principles provide a normative framework for building Islamic value-based collaborative teams with practical applicability in educational institutions. The  study underscores that teamwork development is not only an operational strategy but also amoral and spiritual obligation in Islamic education management.